Econometric methods for research in education - Costas Meghir; Steven Rivkin (Institute for Fiscal Studies (IFS), 2010)
This paper reviews some of the econometric methods that have been used in the economics of education. The focus is on understanding how the assumptions made to justify and implement such methods relate to the underlying economic model and the interpretation of the results. We start by considering the estimation of the returns to education both within the context of a dynamic discrete choice model inspired byWillis and Rosen (1979) and in the context of the Mincer model. We discuss the relationship between the econometric assumptions and economic behaviour. We then discuss methods that have been used in the context of assessing the impact of education quality, the teacher contribution to pupils' achievement and the effect of school quality on housing prices. In the process we also provide a summary of some of the main results in this literature.
Keywords: 330; Bildungsökonomik; Bildungspolitik; Bildungsverhalten; Lehrkräfte; Qualifikation; Schule; Immobilienpreis; Theorie